Cooperative Learning on Promoting Creative Thinking and Mathematical Creativity in Higher Education - Paula Catarino; Paulo Vasco; José Lopes; Helena Silva; Eva Morais (Universidad Autónoma de Madrid, 2019)
Creativity is an indispensable competence for the future of higher education students. Creative thinking skills play an important role in modern society. Creativity is acknowledged as a crucial aspect of the business, research and development or arts. This study presents the assessment results of an intervention using cooperative learning and the conventional teaching method in order to promote creative thinking in higher education. The design used was quasi-experimental pretest and posttest intervention using the Creative Intelligence test (CREA), with experimental and control groups of higher education students of the Communication and Multimedia course in a Linear Algebra class. The participants were 50 students from a Portuguese public university. Results showed that students who participated in the intervention scored significantly higher in the creativity test at the end of the intervention and indicated that creative thinking, and divergent thinking abilities in particular, can be enhanced through the kind of intervention that was proposed in the study.